An Analysis of Appraisal System of Paw Patrol Lyric - Vidhiasi, Dhion Meitreya (Al-Lisan: Jurnal Bahasa, 2021)
Hero-themed children’s films are always fun for children. The PAW Patrol film series is a spectacle aimed at pre-school-age children. The film’s main characters are one 10-year-old child and six puppies. This study aimed to look at the Appraisal System contained in the lyrics of the opening song of the PAW Patrol series, which aired on the NickJr channel. The researcher wanted to find the dominant Appraisal System in the lyrics. The researcher also wanted to know how the lyricist positioned the listeners and viewers of the film through the song’s lyrics. The data analyzed were the lyric of the opening song of the PAW Patrol film series. The data were then analyzed using Martin and White’s Appraisal System theory. Researchers used qualitative descriptive methods in analyzing the data. The results showed the three Appraisal sub-systems; Attitude, Engagement, and Graduation, are found in the lyrics of the PAW Patrol opening song. The dominant appraisal system was Graduation. Listeners or moviegoers are positioned as people who receive the image of the heroic act shown in the song's lyrics.